Advanced accounting - Hoyle, Joe B.; Schaefer, Thomas F.; Doupnik, Timothy S. (Boston : McGraw-Hill / Irwin, 2001)
Business
Keywords: Advanced accounting; Financial statement; Income taxes; Partnerships